The effect of oxygen on the fermentation ability of Saccharomyces cerevisiae during high-gravity wort fermentations - Lodolo, Elizabeth Jacoba (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph.D.) -- University of Stellenbosch, 1999.